High school students' motivation to participate in extracurricular futsal training during the Covid-19 pandemic - Razali; Iqbal, Muhammad (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2022)
The purpose of the study. The purpose of this study was to determine the motivation of the Futsal extracurricular participants at Senior High School. Materials and methods. This research method uses descriptive research with a qualitative approach by analyzing the level of student motivation in following extracurricular activities. the population in this study were futsal extracurricular participants at senior high school in Banda Aceh (Indonesia) which consisted of 40 participants. The sampling technique in this study was total sampling. The instruments used to collect research data were the distribution of questionnaires and interviews and were analyzed with simple percentages. Results. We can conclude that based on the results of this futsal research, 50% said they strongly agreed, 40% said they agreed, 7.5% said they did not agree and 2.5% of participants said they disagreed. Conclusions. The motivation of students in doing futsal extracurricular activities at senior high school negeri 7 Banda Aceh is still a lot of participants who have high motivation to take part in the futsal extracurricular activities but there are also participants who only follow their friends without having a sense of motivation to learn things that are part of the activity of the futsal sport.